Nutritional status and body composition assessment in patients with a new diagnosis of advanced solid tumour: Exploratory comparison of computed tomography and bioelectrical impedance analysis. Issue 3 (March 2021) - Casirati, A.; Vandoni, G.; Della Valle, S.; Greco, G.; Platania, M.; Colatruglio, S.; Lalli, L.; Gavazzi, C.
Summary: Objective: Low skeletal muscle is a common characteristic of cancer-related malnutrition and a predictor of poorer prognosis in oncological patients. In this study we evaluated nutritional status and altered body composition using computed tomography (CT) and bioelectrical impedance analysis (BIA) in newly diagnosed patients. Our purpose was to compare the results of two available techniques to assess body composition suggested by the guidelines and some diagnostic criteria to identify malnutrition. Methods: In a prospective study, patients with a new diagnosis of advanced solid tumour were enrolled and evaluated before starting first-line chemotherapy. Anthropometric, body composition and systemic inflammation measurements were collected and cut-off points from literature data were used for results classification. Malnutrition was expressed as weight loss (WL) in the previous 6 months >10% and underweight body mass index (BMI). Altered body composition was assessed as low index both skeletal muscle (SMI) derived by CT and fat-free mass by BIA (FFMI). Descriptive statistic was presented. Several statistical correlation analyses were performed. Results: 67 patients were assessed: 40M/27F; average age 59 ± 13 years and BMI 23 ± 4; 43 (64%) upper gastrointestinal, 12 lung, 9 colorectal, 3 other cancers. Fourty-five (67%) were malnourished with WL criteria but only 8 (12%) resulted underweight. From analysis of CT images and BIA, 49 (73%) and 10 (15%) patients respectively reported lower cut-off point. Overall, 35 (52%) had both sarcopenia and WL > 10%. Conclusions: Our results suggest that prevalence data of malnutrition expressed as WL are more in agreement with those of sarcopenia recognised using CT than BIA method. Further studies are required to confirm these findings and to identify the best and easiest methods for monitoring BC during nutritional intervention and oncological therapies.